Mathematical statistics - Rietz, H. L. (Henry Lewis), 1875-1943 (Chicago : Published for the Mathematical Association of America by Open Court Publishing Company, 1927)
The MAA is pleased to re-issue the early Carus Mathematical Monographs in ebook and print-on-demand formats. Readers with an interest in the history of the undergraduate curriculum or the history of a particular field will be rewarded by study of these very clear and approachable little volumes. This monograph contributes toward shifting the emphasis and point of view in the study of statistics in the direction of the consideration of the underlying theory involved in certain highly important methods of statistical analysis. With this as the main purpose it is natural that no great effort is made to present a well-balanced discussion of all the many available topics. Considerable portions of this monograph can be read by those who have relatively little knowledge of college mathematics. However, the exposition is designed, in general, for readers of a certain degree of mathematical maturity, and presupposes an acquaintance with elementary differential and integral calculus, and with the elementary principles of probability as presented in various books on college algebra for freshmen.
The nature of the problems and underlying concepts of mathematical statistics -- Relative frequencies in simple sampling -- Frequency functions of one variable -- Correlation -- The Lexis theory -- A development of the Gram-Charlier series.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Mathematical statistics